2022
DOI: 10.1111/jfpp.16394
|View full text |Cite
|
Sign up to set email alerts
|

Laccase‐induced wheat bran arabinoxylan hydrogels from different wheat cultivars: Structural, physicochemical, and rheological characteristics

Abstract: The impact of three arabinoxylan (AX) cultivars (262, 44, 229) on the physicochemical, rheological, and microstructural characteristics of AX hydrogels was explored.The gelation of AX262 was faster and the viscoelastic modulus was higher. During the gelation process, the consumption of ferulic acids was 96%, 87%, and 69% for AX262, AX44, and AX229, respectively, indicating a higher oxidative cross-linking degree of AX262. The decline of adsorption intensity for AX262 hydrogel at 1,644 and 3,423 cm −1 was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(85 reference statements)
1
3
0
Order By: Relevance
“…This can be primarily attributed to the processes of water desorption and thermal decomposition of WEAX. The apparent endothermic peak observed at 30 °C–110 °C was attributed to water evaporation (Kexin et al ., 2022), which is consistent with observations from the TGA curve. Due to its rich hydroxyl group composition, WEAX demonstrates significant water absorption properties, with the water desorption process continuing until the temperature exceeds 110 °C, ultimately reaching equilibrium.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This can be primarily attributed to the processes of water desorption and thermal decomposition of WEAX. The apparent endothermic peak observed at 30 °C–110 °C was attributed to water evaporation (Kexin et al ., 2022), which is consistent with observations from the TGA curve. Due to its rich hydroxyl group composition, WEAX demonstrates significant water absorption properties, with the water desorption process continuing until the temperature exceeds 110 °C, ultimately reaching equilibrium.…”
Section: Resultssupporting
confidence: 92%
“…In this study, WEAX was extracted with a calculated A/X ratio of 0.87, indicating a high degree of branching similar to the reported A/X ratio of wheat AX at 0.9 (Jinxin et al ., 2023). Research has demonstrated that AX with increased branching exhibits enhanced water solubility, gel properties, and prebiotic potential (Nianxia et al ., 2019; Kexin et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ester-linkage band was located at 1644 cm −1 , which could be overlapped with the amide I band [39]. The signal intensities of LAC and LAC + FA decreased at 1644 cm −1 , possibly because of the higher degree of FA oxidation during AX gel formation [40]. Generally, there are two ways of FA dimerization: the self-crosslinking of AX feruloyl radicals [41] and cross-linking of FA radicals with nucleophilic residues in protein chains with subsequent FA covalent cross-linking [14].…”
Section: Functional Groups Vibration Analysismentioning
confidence: 95%